Positive predictive values and outcomes for uninformative cell‐free DNA tests: An Italian multicentric Cytogenetic and cytogenomic Audit of diagnOstic testing (ICARO study). (30th November 2022) - Grati, Francesca Romana; Bestetti, Ilaria; De Siero, Daria; Malvestiti, Francesca; Villa, Nicoletta; Sala, Elena; Crosti, Francesca; Parisi, Valentina; Nardone, Anna Maria; Di Giacomo, Gianluca; Pettinari, Antonella; Tortora, Giada; et al.
Abstract: Objectives: To establish the positive predictive values (PPV) of cfDNA testing based on data from a nationwide survey of independent clinical cytogenetics laboratories. Methods: Prenatal diagnostic test results obtained by Italian laboratories between 2013 and March 2020 were compiled for women with positive non‐invasive prenatal tests (NIPT), without an NIPT result, and cases where there was sex discordancy between the NIPT and ultrasound. PPV and other summary data were reviewed. Results: Diagnostic test results were collected for 1327 women with a positive NIPT. The highest PPVs were for Trisomy (T) 21 (624/671, 93%) and XYY (26/27, 96.3%), while rare autosomal trisomies (9/47, 19.1%) and recurrent microdeletions (8/55, 14.5%) had the lowest PPVs. PPVs for T21, T18, and T13 were significantly higher when diagnostic confirmation was carried out on chorionic villi (97.5%) compared to amniotic fluid (89.5%) ( p  < 0.001). In 19/139 (13.9%), of no result cases, a cytogenetic abnormality was detected. Follow‐up genetic testing provided explanations for 3/6 cases with a fetal sex discordancy between NIPT and ultrasound. Conclusions: NIPT PPVs differ across the conditions screened and the tissues studied in diagnostic testing. This variability, issues associated with fetal sex discordancy, and no results, illustrate the importance of pre‐ and post‐test counselling. Key points: What's already known about this topic? The reported performance of cfDNA testing by NIPT laboratories is often based on incomplete follow‐up. Data from cytogenetics laboratories can provide an alternative, independent, assessment on the positive predictive value (PPV), risk in cases when there is no result, and help explain contradictory fetal sex assignments. Prior cytogenetic laboratory studies assessing PPV from have been based on small numbers of cases. What does this study add? PPV is higher when the diagnostic testing is based on CVS compared to amniocentesis, presumably because CVS includes cases with confined placental mosaicism. In a high proportion of no result cases, a cytogenetic abnormality may be present. Therefore, these do need to be considered high‐risk pregnancies. Diverse disorders of sexual development can be present when fetal sex assignments based on ultrasound and NIPT are discordant.